YWCA's 75th anniversary food table - Unknown:::Creator::::::::::::
Photograph shows a long table with food and a large floral decoration on it for the YWCA's celebration of it's 75 years in San Jose. There are also small round dining tables and chairs with small floral decorations on them in the background.